Live Simultaneous Interpreting of Political Speeches into Arabic - Al-Nashash, Maysa (2006)
A Master of Arts Thesis in English Arabic/Arabic English Translation and Interpreting Submitted to the College of Arts and Sciences by Maysa Al-Nashash Entitled, "Live Simultaneous Interpreting of Political Speeches into Arabic," December 2006. Available are both Soft and Hard Copies of the Thesis.